Desenvolvimento e metabolismo de plantas e frutos de meloeiro amarelo sob estresse salino - Araújo, Beatriz de Abreu (2023)
Water scarcity, a recurring theme of global concern, is one of the main problems for agriculture in the Brazilian Northeast. In this region, melon production is concentrated in Brazil and almost all of the water used in its irrigation comes from deep wells, the vast majority of which have a high salt content. Therefore, the use of saline water for melon irrigation in the Brazilian Northeast is imperative and rational management is necessary, based on technical-scientific data. Given this, the research aimed to evaluate the effects of using saline water on plant growth, production, fruit quality and fruit metabolism of yellow melon variety Goldex. The research was conducted in the field at the Pacajus Experimental Station in a completely randomized design with two salinity levels of irrigation water (0.8 and 4.0 dS m-1) and eight evaluation times (52, 54, 56, 58 , 60, 62, 64 and 66 DAT) where the growth of plants and fruits and the production and quality of these fruits were evaluated. In a protected environment, the research was conducted at Embrapa Agroindústria Tropical, in Fortaleza, Ceará, in a greenhouse. The experimental design was conducted in randomized blocks, with four electrical conductivities of irrigation water (1.5, 2.5, 3.5 and 4.5 dS m-1) and four stages of development (48, 54, 60 and 64 DAT), where plant growth, production, post-harvest quality and fruit metabolism were evaluated. Under field conditions, salinity (4.0 dS m-1) reduced plant growth, leaf area and branch length, while fruit production and post-harvest quality were not affected by saline stress. In a protected environment, there was an increase in gas exchange and chlorophyll index and a reduction in leaf area (30% reduction in salinity of 4.5 dS m-1) and fruit mass. The concentration of total soluble solids was not compromised under salt stress conditions. The metabolism of melon fruits underwent slight changes due to saline